THU0196 Is the Basdai Score Driven by Pain in Ankylosing Spondylitis Patients Treated with Anti-TNF?. (9th June 2015) - Rahman, P.; Jovaisas, A.; Bensen, W.; Olszynski, W.; Jaroszynska, A.; Baer, P.; Sheriff, M.; Sholter, D.; Psaradellis, E.; Sampalis, J.S.; Nantel, F.; Otawa, S.; et al.
Abstract : Background: The present standard for measuring disease activity in Ankylosing Spondylitis (AS) is the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) which focuses on five major symptoms including fatigue, axial pain, peripheral pain, enthesitis and morning stiffness (severity and duration). Objectives: Given that the BASDAI instrument contains two pain questions, the objective was to assess whether pain symptoms are the main drivers of BASDAI scores among AS patients treated with anti-TNFs in routine clinical practice. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with infliximab (IFX) or golimumab (GLM). Patients with AS treated with IFX or GLM and enrolled between 2005 and 2014 were included in this analysis. A modified weighted BASDAI score (m-BASDAI) was calculated excluding the axial (Q2) and peripheral (Q3) pain questions of the BASDAI. The correlation of BASDAI, each of its components, and the modified BASDAI (m-BASDAI) was assessed with the Pearson correlation coefficient. BASDAI low disease activity (LDA) and m-BASDAI LDA were defined as a score ≤3. The association between the number of administered analgesics (0, 1, >1) and BASDAI/m-BASDAI was assessed with one-way ANOVA. Results: A total of 413 AS patients with 1, 709 assessments were included in this analysis. Correlation analysis showed a strong correlation between the full BASDAI and m-BASDAI scores (r=0.98, P<0.001). With respect to the individual BASDAI questions, a strong positive linear correlation was observed between all questions and the BASDAI score as well as the m-BASDAI score. As expected, a lower correlation was observed between Q2 and Q3 with the m-BASDAI relative to BASDAI. Axial pain was most strongly correlated with the severity of morning stiffness, whereas the highest correlation of peripheral pain was observed with localized tenderness. The cross-tabulation of BASDAI LDA and m-BASDAI LDA showed a strong measure of agreement (kappa=0.871, P<0.001). Omission of the pain questions from BASDAI resulted in a comparable proportion of LDA cases (41.7% vs. 40.9%) when using the same LDA definition. Increased use of analgesics (0 vs. 1 vs. >1) over 2 years of follow-up was associated with significantly (P<0.05) higher mean scores in BASDAI, m-BASDAI, and each of the BASDAI components. No significant association was observed between increased use of analgesics and treatment retention. Conclusions: Higher levels of AS pain are significantly associated with a higher BASDAI score and increased use of analgesic medications among patients treated with anti-TNFs. In addition to pain, fatigue, tenderness, and morning stiffness are likewise important contributing components in the BASDAI score and the disease burden of AS. Disclosure of Interest: P. Rahman Consultant for: Abbott, AbbVie, Amgen, BMS, Celgene, Janssen, Novartis, Pfizer, Roche, A. Jovaisas: None declared, W. Bensen Consultant for: Janssen, W. Olszynski: None declared, A. Jaroszynska: None declared, P. Baer Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, M. Sheriff: None declared, D. Sholter: None declared, E. Psaradellis Employee of: JSS Medical Research, J. Sampalis Shareholder of: JSS Medical Research, F. Nantel Employee of: Janssen, S. Otawa Employee of: Janssen, A. Lehman Employee of: Janssen, C. Tkaczyk Employee of: Janssen, M. Shawi Employee of: Janssen